Pengaruh faktor-faktor resiliensi terhadap kesiapan transformasi digital di UKM - Faizatul Amalia; Ardaneswari Dyah Pitaloka Citraresmi; Andan Linggar Rucitra; Siti Asmaul Mustaniroh; Widhistya Kartikaningrum (AGROINTEK, 2024)
SMEs face the problem of readiness and resilience in implementing digital transformation as part of the industrial revolution. Therefore, a process is needed to identify resilience factors that can increase the readiness of SMEs toward Industry 4.0. The industrial revolution 4.0 that emerged in recent years requires businesses and society to be ready to implement digital transformation. This study aims to identify the effects of resilience factors in the form of people, processes, and technology that influence the adoption of digital transformation in SMEs. The research object is SMEs in various sectors with a literature study approach to develop a conceptual framework and data collection using a questionnaire. Construct testing and data analysis used statistical methods from confirmatory factor analysis, while the data testing process used the Partial Least Square (PLS) method. The results of the study show that the resilient people (RPe) factor has a weak influence on international orientation (IO) but has a strong direct influence on digital transformation readiness (DT). The resilient process (RPo) and resilient technology (RTe) factors weakly influence DT but are significant on IO. Meanwhile, the IO factor has a strong influence on DT. As a mediator, IO has a weak role in mediating Rpe and DT but significantly mediates RPo, and RTe against DT. The results also show that an independent attribute of 65.9% influences DT, while IO has an independent attribute effect of 41%. The findings guide SMEs to pay attention to aspects of resilience in the work system and have a global orientation in business development plans to be more ready to adopt digital transformation.